235. If Symptoms Aren't Described, Antibiotics Aren't Prescribed: Implementation of a Multifaceted Toolkit Targeting Overtreatment of Asymptomatic Bacteriuria across a Large Health-system. (26th November 2018) - Williamson, Julie E; Logan, Andrea Y; Boger, M Sean; Jarrett, Steven; Irausquin, Stephanie J; Davidson, Lisa
Abstract: Background: Overtreatment of asymptomatic bacteriuria (ASB) is a major challenge for antimicrobial stewardship (ASP). A February 2017 review of our health-system showed >50% of inpatients with a positive urine culture (PUC) were treated despite no urinary tract infection (UTI) symptoms or compelling indications (CI) [pregnancy or pending urologic procedure]. In Fall 2017, we piloted a multifaceted toolkit (MTK) to support an ASB educational campaign (EC) at 26 hospitals. Methods: A MTK of flyers, a urinary testing algorithm, and narrated slides (Figure 1) was distributed in Fall 2017 and implementation was customized by each hospital's ASP. Impact of EC on treatment of patients with no urinary symptoms (NUS) or altered mental status (AMS) alone were assessed retrospectively by sampling inpatient PUCs from February 1–28, 2018 in a manner identical to a pre-EC sample. Patients were excluded if: CI, age <18 years, neutropenic, or admitted on UTI therapy or with nephrolithiasis. Demographic, clinical, and laboratory data; UTI symptoms; microbiology results; and antimicrobial therapy received, were collected via an adapted CDC UTI assessment form. Each hospital was surveyed on MTK implementation. Results: Preliminary pre- and post-EC data from the same 14 hospitals are shown. Patients with NUS decreased slightly post-EC, while those with ≥1-specific symptom increased. Treatment of those with NUS declined post-EC, and those with AMS alone received less empiric therapy. Twelve hospitals (86%) completed the MTK survey. Six used all components, five some, and one none. Those who implemented the MTK cited flyers and slides as most useful and preferred the AMS flyer. Although available, only 55% of hospitals affirmed provider algorithm use. Conclusion: Post-EC, less patients with a PUC: had NUS, those with NUS were less likely to be treated, and those with AMS alone received less empiric therapy. MTK implementation appeared to impact ASB treatment, and perhaps, testing. Lower use of the testing algorithm may signal a need for simplification. More data are needed to identify which component(s) of the MTK are most effective. Disclosures: L. Davidson, Duke Endowment: Grant Investigator, Grant recipient